Proteomics of Pyrococcus Furiosus(Pfu): Identification of Extracted Proteins by Three Independent Methods - Wong, Catherine C.L. (2013)
Pyrococcus Furiosus (Pfu) is an excellent organism to generate reference samples for proteomics labs because of its moderately sized genome and very little sequence duplication within the genome. We demonstrated a stable and consistent method to prepare proteins in bulk that eliminates growth and preparation as a source of uncertainty in the standard. We performed several proteomic studies in different laboratories using each laboratory's specific workflow as well as separate and integrated data analysis. This study demonstrated that a Pfu whole cell lysate provides suitable protein sample complexity to not only validate proteomic methods, work flows, and benchmark new instruments, but also to facilitate comparison of experimental data generated over time and across instruments or labs.